Financial de-dollarization in Bolivia - Del Río Rivera, Marco Antonio; Montero Kuscevic, Casto Martín (Estudios Económicos de El Colegio de México, 2014)
Using data for the period 1990-2010 and a portfolio optimization approach, we identify the causes of the process of financial de-dollarization in Bolivia (bolivianization). Cointegration tests showed the existence of a long-run relationship between de-dollarization and the optimizing portfolio approach. Additionally, we found that the Tax to Financial Transactions and the exchange rate spread are the most influential variables to determine bolivianization.